Complete introduction to Protocol Buffers 3 - Maarek, Stéphane (Packt Publishing, 2018)
"Protocol Buffers (Protobuf) is a fundamental data serialization format that every data engineer should know about. It is leveraged by many top tech companies such as Google and enables micro-services to transfer data in a format that is safe and efficient. In just a few hours, you will know everything you need to know to create simple and complex .proto files, and write code in your favourite programming languages such as Java, Python and Go. Protocol Buffers generates all the boilerplate code for you! This is the course that could change your data skills. Learning and getting hands-on on Protocol Buffers helps you to enhance your career opportunities and helps to boost your income. An investment in your career is an investment in yourself. Don't procrastinate. There is no time like the present to take charge of your career. Take your career to the next level by learning Protocol Buffers today!"--Resource description page